Risk of current suicidal ideations associated with lifelong anhedonia and recent change of anhedonia in individuals with insomnia: A cross-sectional study. (June 2022) - Dosogne, Marjorie; Wacquier, Benjamin; Al Faker, Mohammed; Willame, Hadrien; Point, Camille; Loas, Gwenolé; Hein, Matthieu
Abstract: Background: Individuals with insomnia are a subpopulation at high-risk of suicide. However, despite the elements in favour of an implication of anhedonia in the occurrence of current suicidal ideations (SI), no study has investigated the role played by this affective symptom in the occurrence of current SI in individuals with insomnia. The aim of this study was to investigate the risk of current SI associated with lifelong anhedonia and recent change of anhedonia in individuals with insomnia. Method: Demographic and polysomnographic data from 493 individuals with insomnia selected retrospectively from the clinical database of the Erasme Hospital Sleep Laboratory were analysed. Current SI were considered present if the score in item 9 of the Beck Depression Inventory (BDI-II) was ≥1 and/or if they were highlighted during the systematic psychiatric assessment conducted on admission to the Sleep Laboratory. Logistic regression analyses were used to determine the risk of current SI associated with anhedonia in individuals with insomnia. Results: The prevalence of current SI was 21.5% in our sample of individuals with insomnia. After adjusting for major confounding factors, multivariate logistic regression analyses demonstrated that unlike lifelong anhedonia, only recent change of anhedonia was a risk factor for current SI in individuals with insomnia. Conclusion: In this study, we demonstrated that in individuals with insomnia, recent change of anhedonia is a risk factor for current SI, which seems to justify more systematic research and adequate therapeutic management of this condition to allow better prevention in this particular subpopulation at high-risk of suicide. Highlights: Current SI are frequent (21.5%) in subjects with insomnia. Recent change of anhedonia is risk factor for current SI in subjects with insomnia. Lifelong anhedonia is not risk factor for current SI in subjects with insomnia. Adequate management of anhedonia is essential in subjects with insomnia.